The impact of US Monetary Policy Announcements on Equity Prices: Evidence from Borsa Istanbul - İkizlerli, Deniz; Yener, Haluk; Eroğlu, Burak Alparslan (My University, 2020)
This study examines the effect of FOMC's (Federal Open Market Committee) announcements on the volatility of stock returns in the Borsa Istanbul (BIST) from January 4, 2000 to May 31, 2019. We find that FOMC's news increases the market level of volatility on announcement days but cannot find any evidence that it had a destabilizing effect on the Turkish stock market over our observation period. We also look at the effect of FOMC's news on the return volatility of the BIST100 index over different states of the stock market and find that FOMC's announcement days give a lift to conditional volatility both in bull periods and bear periods, but find no evidence of destabilizing impact. On the contrary, both positive announcement and negative announcement shocks in bull periods are found to depress volatility on consecutive days. In other words, FOMC's announcements in bull periods have a stabilizing effect on equity prices rather than a destabilizing in the BIST100 index.
Keywords: FOMC's (Federal Open Market Committee) Announcements; StockReturn Volatility; Asymetric Volatility; Emerging Markets